Synthesis of Heptylalkanoyldisulfides and Investigation of Their Antimicrobial Properties - Aliyev, Fuad; Azizova, Sara (JOURNAL OF ADVANCES IN CHEMISTRY, 2023)
The paper describes the results of the research of some heptylalkanoyldisulfides as antimicrobial additives to the lubricating oils. Heptylalkanoyldisulfides were synthesized and studied. The synthesized compounds were characterized by spectroscopic techniques. Study of antimicrobial properties of the studied heptylalkanoyldisulfides revealed effective bactericidal and fungicidal activities in suppression of fungi and bacteria allowing them to be used as biocides in storage and transportation of oil products. Antimicrobial efficacy of the studied compounds was determined by zonal diffusion method using the following microorganisms: bacteria, fungi and yeast. The test compounds were added to M-8 oil in mass percent. It is established that their antimicrobial activity is at the level of effectiveness of the widely used industrial additive sodium pentachlorophenolate. Sodium pentachlorophenolate, widely applied as an antimicrobial additive in lubricating oils, was used for comparison. It was determined that they may be used as antimicrobial additives for M-8 engine oil (0.25-1%). As a result of the studies carried out on heptylalkanoyldisulfides, distinct patterns of dependence of antimicrobial efficacy on the structure of alkyl radical were determined. Antimicrobial activity increases by an increase in alkyl radical, i.e., each subsequent member of the disulfide series is biologically more active than the previous one. The increase in antimicrobial activity seems to be due to the fact that the adding each new CH2 group gives one more van der Waals bond, increasing adsorption forces that bind the compound to the receptor in the microorganism. As a result of the studies carried out on heptylalkanoyldisulfides, distinct patterns of dependence of antimicrobial efficacy on the structure of alkyl radical were determined